Early treatment of anterior open bite (Research, Society and Development, 2025)
This study aimed to analyze, through a narrative review, the early treatment of anterior open bite, highlighting its main characteristics and the most commonly used interventions. Anterior open bite is characterized by a type of malocclusion that is highly prevalent in young patients where there is a negative vertical overlap between the anterior teeth. Selected studies that directly addressed anterior open bite were used for the development of this work. The results showed how this condition can be classified as dentoalveolar and skeletal, directly interfering with the growth and development of facial structures, thus impairing the basic functions of the stomatognathic system such as chewing, phonetics, swallowing, facial growth and aesthetics. Anterior open bite presented a multifactorial etiology including genetic and environmental causes; factors that generate the worsening of this condition over time, leading to great difficulty in the therapeutic approach. It was concluded that early treatment in cases of dentoalveolar anterior open bite is based on the interruption of deleterious habits, and in situations of skeletal origin, it is based on orthopedic growth control. Therefore, early intervention is extremely important to achieve adequate growth of the maxillomandibular joint, thus avoiding more complex interventions later on.